Capital flows to emerging economies and global risk aversion during the COVID-19 pandemic - Carlos Alba; Gabriel Cuadra; Juan R. Hernández; Raúl Ibarra-Ramírez (Banco de México, 2021)
This paper analyzes recent changes in the relative importance of the determinants of capital flows to emerging market economies. For this purpose, we estimate vector autoregressive (VAR) models for the period 2009-2020. Based on these models, we estimate the effects on debt flows from shocks to their determinants. Then, we quantify the contribution of each of the variables included in the model to explain the evolution of these flows in each month of the sample through a historical decomposition analysis. The main results indicate that the contribution of global risk aversion to explain the evolution of debt flows increased during March 2020 compared to the past, although its relative importance has decreased since, particularly as the performance of financial markets improved.
Keywords: F21; F32; F41; G15; 330; Capital Flows; Global Risk Aversion; COVID-19; Vector Autoregression